Inventory Management System based on IoT and Microservices Architecture Design - Sithiyopasakul, Paisan; Piyatananugoon, Chavinkorn; Chaowalittawin, Vasutorn; Krungseanmuang, Woranidtha; Sathaporn, Posathip; Kanjanasurat, Isoon; Purahong, Boonchana; Archevapanich, Tunjai; Lasakul, Attasit (My University, 2023)
This paper presents the inventory management system based on IoT and microservices architecture that synced between IoT (Internet of Things) and web application. There are two main parts consisting of IoT forklift vehicle and data transmitted system by MQTT protocol. Microservice can utilize data to process business logic and provides API. Inventory area includes a zone, a subzone and parking area for forklifts to scan QR code on each subzone. Data of forklifts is published to back-end service. The results of system microservice publish information events and processes business data to the admin client with a delay under a second.
Keywords: API; Inventory Management; IoT; Microservices; MQTT